Cellular fibroepithelial lesions diagnosed on core needle biopsy: Is there any role of clinical‐sonography features helping to differentiate fibroadenomas and phyllodes tumor?. Issue 3 (12th May 2020) - Al‐Arnawoot, Basma; Scaranelo, Anabel; Fleming, Rachel; Kulkarni, Supriya; Menezes, Ravi J.; McCready, David; Done, Susan; Freitas, Vivianne
Abstract: Objective: The purpose of this study is to determine the role of clinico‐sonographic features of breast cellular fibroepithelial lesions (CFELs) diagnosed on core needle biopsy (CNB) in the differentiation between fibroadenoma (FA) and phyllodes. Materials and Methods: Results of consecutive women with a CNB showing CFEL from 2005 to 2010 were retrospectively reviewed. Clinical and sonographic findings were compared with surgical outcomes. Chi‐square and Fisher's exact tests were used followed by a regression model for statistical analysis. Results: A total of 131 women with 134 CFEL were included in the study; 89 (66%) were FAs and 45 (34%) were phyllodes (32 benign; 13 malignant). Significant predictors of increased risk of phyllodes tumor were patient age equal to or greater than 50 years ( P = .021) and lesion size less than 2 cm at sonography ( P = .043). No other imaging or clinical features were able to differentiate FA from phyllodes tumors. Conclusion: CFEL with a larger size in older women is associated with the surgical pathological result of phyllodes tumor and management should be tailored accordingly. Younger patients with small size nodules might be approached less aggressively, depending on a personalized discussion with the surgeons, taking into account the results obtained in this study.